“ATOMIC LAW” OR “NUCLEAR LAW”? AN ACADEMIC DISCUSSION REVISITED - J. Handrlica (BRICS Law Journal, 2018)
The terms “atomic law” and “nuclear law” are regularly being (to a certain part as synonyms) used in both scientific and popular literature to refer to a body of legal norms, governing peaceful uses of nuclear energy and ionizing radiation, as provided by sources of international law (“international atomic law,” or “international nuclear law”), national legislation and a complex body of unbinding norms (soft law). Further, several other variations of these terms are also regularly used (such as “atomic energy law,” “nuclear energy law,” “international nuclear law,” “law of the atomic/nuclear energy,” etc.). This contribution aims to identify the origins of this terminological labyrinth and to deal with the perception of these terms in the legal scholarship. Further, this contribution deals with the recent perception of these terms in the legal science of major States, using nuclear energy for peaceful purposes. This article aims to clarify the existing terminology, which is to large extent being used in the literature without an appropriate explanation. The author pleads for a consequent use of the term “nuclear law” (droit nucléaire, yadernoe pravo, Nuklearrecht, derecho nuclear, diritto nucleare) and presents arguments for such conclusion.